Critical analysis of models of teacher educators’ preparation in Singapore and Tanzania - Saimon, Musa (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2022)
Despite the fact that teacher education determines the quality of teachers in a given country, various countries adopt various models of teacher educators’ preparation. Since such models vary in their effectiveness, it has led to some countries being far ahead of others in terms of the quality of their teacher education. Consequently, there has been a growing interest among researchers in comparing teacher education models of different countries as a way of revealing lessons that countries can learn from one another in relation to the models they adopt. Therefore, the present study aimed at comparing critically teacher education models adopted in Tanzania and Singapore to highlight lessons that Tanzania can learn from Singapore.  The study was guided by the following questions: a) what are the models for teacher educators’ education in Singapore and Tanzania; b) how effective are the models used for teacher educators’ education in Singapore and Tanzania? The study revealed various models adopted in both Tanzania and Singapore. It has also examined the effectiveness of the revealed models. The study calls for Tanzania education system to link policies and practices with research findings and to centralized teacher education to improve its quality.